Always on my mind: Cross-brain associations of mental health symptoms during simultaneous parent-child scanning. (December 2019) - Cosgrove, Kelly T.; Kerr, Kara L.; Aupperle, Robin L.; Ratliff, Erin L.; DeVille, Danielle C.; Silk, Jennifer S.; Burrows, Kaiping; Moore, Andrew J.; Antonacci, Chase; Misaki, Masaya; Tapert, Susan F.; Bodurka, Jerzy; et al.
Highlights: We tested neural associations of dyadic mental health symptoms in error processing. Parent depression positively associated with parent dorsolateral PFC activity. Parent anxiety positively associated with adolescent anterior insula activity. Adolescent depression/anxiety negatively associated with parent default mode activity. In sum, results suggest mental health symptoms may have dyadic neural effects. Abstract: How parents manifest symptoms of anxiety or depression may affect how children learn to modulate their own distress, thereby influencing the children's risk for developing an anxiety or mood disorder. Conversely, children's mental health symptoms may impact parents' experiences of negative emotions. Therefore, mental health symptoms can have bidirectional effects in parent-child relationships, particularly during moments of distress or frustration (e.g., when a parent or child makes a costly mistake). The present study used simultaneous functional magnetic resonance imaging (fMRI) of parent-adolescent dyads to examine how brain activity when responding to each other's costly errors (i.e., dyadic error processing) may be associated with symptoms of anxiety and depression. While undergoing simultaneous fMRI scans, healthy dyads completed a task involving feigned errors that indicated their family member made a costly mistake. Inter-brain, random-effects multivariate modeling revealed that parents who exhibited decreased medial prefrontal cortex and posterior cingulate cortex activation when viewing their child's costly error response had children with more symptoms of depression and anxiety. Adolescents with increased anterior insula activation when viewing a costly error made by their parent had more anxious parents. These results reveal cross-brain associations between mental health symptomatology and brain activity during parent-child dyadic error processing.